The difference between political and philosophical freedom - Ga'far, Khadeega (AUC Knowledge Fountain, 2015)

(untitled)
Hannah Arendt distinguishes between two different practices of freedom whose origins are rooted into two historical human experiences: political freedom/action and philosophical freedom/free will. She argues that the two experiences were different as concerns the origin, the location and the conditions of each. Freedom of the will, or philosophical freedom, is relevant only in solitude while political freedom is relevant to people living together in political communities. Arendt also claims that the freedom of the will is the origin of the ideal of sovereignty which constitutes its meaning in commanding and demanding obedience. Hence, the free will realizes its freedom at the expense of oppressing one’s self and oppressing others. In addition to presenting the Arendtian accounts on the two types of freedom, I shall argue that Arendt’s notion of new beginnings is an attempt to transform the faculty of will from a faculty which realizes itself in commanding, either itself or others, to a faculty that realizes itself in initiating new beginnings with others in the public realm.